A Kinetic Study on the Degradation of Acetaminophen and Amoxicillin in Water by Ultrasound. Issue 47 (17th December 2020) - Stucchi, Marta; Rigamonti, Marco G.; Carnevali, Davide; Boffito, Daria C.
Abstract: This paper presents a study of the conversion pathway of acetaminophen (APAP) and amoxicillin (AMO) in water by ultrasound as a single degradation method. Results showed that the sonication power output, continuous vs. pulsed ultrasound and starting concentration, result in different conversion pathways, as well as the simultaneous presence of the two molecules reduces the degradation yield. Hydroquinone and hydroxyl‐hydroquinone were detected as acetaminophen by‐products, while amoxicillin degraded into four main products. Accordingly, we proposed a conversion pathway mechanism and we finally regressed the amoxicillin conversion kinetics as a function of the ultrasonic power. APAP was more resistant to continuous sonication either at low (25 ppm) or high (100 ppm) starting concentration. On the contrary, ultrasound was able to convert AMO up to 56 % starting from a concentration of 25 ppm. We ascribed this behavior to the presence of a higher number of hydroxyl groups present in the molecule compared to APAP. Moreover, when ultrasound were applied in pulses, it resulted in an energy saving of more than 50 % for a 2 % lower AMO conversion. Abstract : The conversion of acetaminophen and amoxicillin has been studied by ultrasound, without any other treatment. The purpose is investigating the role of US and their effect on organic matter, in different conditions. The sonication power influences the degradation, but it depends primarily on the molecular structure of the substrate. The initial concentration influences the degradation rate and also the simultaneous presence of two molecules strongly affect the effect of US.